Behavioural and breeding ecology of a population of European nightjar Caprimulgus europaeus - Rayner, Jack (2016)
A breeding population of European nightjar Caprimulgus europaeus in Nottinghamshire was monitored over the course of the 2015 breeding season, and analysed alongside data recorded in previous seasons in order to investigate features of the species’ behavioural, breeding and population ecology. Of particular interest were the details of the nightjar mating system, about which relatively little is known, and potential effects of nearby recreational human disturbance, which are often suggested to have a negative impact upon nightjar nest abundance and success. Results from the study into the effects of human recreational disturbance upon breeding nightjars and nest success rates suggested that differing forms of human site visitation may have contrasting effects. Particularly, numbers of walkers and dogs were generally negatively associated with habitat productivity measured as the number of fledglings produced, and site occupancy by paired males, while relatively non-invasive visitation by cyclists appeared positively associated with these same measures. With regard to the nightjar mating system more generally, results from GPS tracking of individuals demonstrated significant differences in nightly range sizes and distances from roosts over the course of the night between males of paired and unpaired breeding statuses, with unpaired males tending to exhibit a greater range of movement, and appeared to indicate a likelihood of extra-pair copulations. Larger area of sexually dimorphic white spots on the male plumage was found to be strongly and positively related with muscle score, which was considered an honest indication of male quality, and it is suggested that these white spots may play a role in courting and dominance interactions. Results from genetic analyses provided some support for the hypothesis that mate switching by females may occur between broods, while geographically nearby populations were not genetically differentiated. There were significant genetic differences among breeding populations between seasons, and the population did not appear to be at Hardy-Weinberg equilibrium. It is suggested that this could provide an indication of movement between breeding sites by migratory individuals. Overall, the results of this study of nightjar ecology provide insight into the effects upon breeding nightjar of nearby human recreational disturbance, the nightjar’s breeding ecology more generally, and some elements of nightjar population ecology. The results suggest that the impacts of human recreational disturbance may not ￼necessarily be negative so long as the disturbance is non-invasive, and also that males appear to compete for females, with both sexes potentially mating with multiple partners. Recommendations are made for future research in a number of areas, with a suggested focus upon migratory movements following the results of the genetic analyses, with applications in the conservation and understanding of the habits of this cryptic species.